Comparison of Neutrophil-Lymphocyte Ratio in Patients with COVID-19 and Dengue Hemorrhagic Fever - Tenri Esa; Uleng Bahrun; Adeline Nurul Hasanah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Coronavirus Disease-19 (COVID-19) and Dengue Hemorrhagic Fever (DHF) can be found together in patients and are difficult to distinguish because they have the same antigenic viral structure, symptoms, and laboratory findings. Neutrophil-Lymphocyte Ratio (NLR) is one of the inflammatory markers that are both easy and have fast results, so it is considered adequate for managing both diseases. This study aimed to compare NLR values and cut-off based on degrees in COVID-19 and DHF patients. The study used data from medical records of 459 COVID-19 patients and 95 DHF patients treated at UNHAS RSPTN and Sayang Rakyat Hospital from July 2020 to August 2021. They had routine hematological examination results when they were first admitted. COVID-19 samples were grouped into severe and moderate degrees, and DHF samples were grouped into DHF without shock and DHF in shock. Mann-Whitney test, independent T-test, and ROC curve were used to compare the two groups (significant if the p-value was <0.05). There was a difference in NLR median between moderate COVID-19 (2.57) and severe COVID-19 (6.39) (p<0.001); between DHF without-shock (0.49) and DHF in-shock (0.43) (p<0.001). Neutrophil lymphocyte ratio cut-off between moderate and severe COVID-19 based on ROC curve was 5.66 (sensitivity 79.6%, specificity 73.5%), and between DHF without-shock and DHF in-shock was 0.39 (sensitivity 93.2%, specificity 83.3%). Neutrophil lymphocyte ratio values in COVID-19 are different from DHF. Neutrophil-lymphocyte ratio values are higher in severe COVID-19 than moderate, while NLR values are lower in DHF in shock rather than without shock.